Case Report: Venetoclax combined with hypomethylating agents for the treatment of newly diagnosed with mixed-phenotype acute leukemia and a literature review - Mi, Ruihua; Guo, Shuli; Yang, Weidong; Wang, Lin; Ma, Yixuan; Chen, Lin; Li, Dongbei; Wei, Xudong (Frontiers in Oncology, 2025)
ObjectiveTo investigate the efficacy and safety of venetoclax (Ven) in combination with hypomethylating agents (HMAs) for the treatment of mixed-phenotype acute leukemia (MPAL).MethodsFrom July 2023 to April 2025, 4 newly diagnosed MPAL patients treated with Ven combined with HMAs at the Affiliated Cancer Hospital of Zhengzhou University, Luoyang Central Hospital and Anyang Regional Hospital were retrospectively analyzed to determine the efficacy and safety of this treatment. The relevant published studies were reviewed.ResultsThis study included four patients (2 males, 2 females) with a median age of 47 years (range: 40–80 years). Three patients were classified as having B/myeloid MPAL, and one was classified as having T/myeloid MPAL. All patients achieved complete remission (CR) after one cycle of venetoclax combined with HMAs. Notably, Patient 3, who tested positive for the BCR::ABL1 fusion gene, received additional tyrosine kinase inhibitor (TKI) therapy. The median duration of myelosuppression during induction therapy was 26 days (range: 7–36). Patients 1 and 4 developed infections during induction, which were controlled with aggressive antimicrobial treatment and supportive care. In contrast, Patients 2 and 3 tolerated the regimen well without significant adverse events.ConclusionThe treatment of MPAL with Ven combined with HMAs achieved a high remission rate and can be used as an alternative treatment for MPAL.